2012
DOI: 10.4028/www.scientific.net/amr.538-541.2536
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Torsional Dynamic Properties of Hydraulic Excavator Slewing Transmission Mechanism

Abstract: A hydraulic excavator is taken as the object to study. Considering the characteristics of slewing transmission mechanism of hydraulic excavator, the torsional vibration equation is established by the finite element method. According to the torsional vibration equation, the effects of the equivalent moment of inertia of working device on the torsional dynamic properties of slewing transmission mechanism are analyzed. Using the optimization theory, the mathematical model is built, which is by means of the equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The electrochemical activity of the supercapacitor is greatly influenced by the electrode material [11–17] . Recent research has shown that battery‐like electrodes with a quick interfacial Faradaic reversible redox reaction process that takes place on the electrode surface and have substantial potential for all‐solid‐state supercapacitor (ASSSC) technology.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical activity of the supercapacitor is greatly influenced by the electrode material [11–17] . Recent research has shown that battery‐like electrodes with a quick interfacial Faradaic reversible redox reaction process that takes place on the electrode surface and have substantial potential for all‐solid‐state supercapacitor (ASSSC) technology.…”
Section: Introductionmentioning
confidence: 99%